2010
DOI: 10.1002/jcp.22130
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin/kexin type 9 (PCSK9) affects gene expression pathways beyond cholesterol metabolism in liver cells

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) induces degradation of low-density lipoprotein receptor (LDLR) in the liver. It is being pursued as a therapeutic target for LDL-cholesterol reduction. Earlier genome-wide gene expression studies showed that PCSK9 over-expression in HepG2 cells resulted in up-regulation of genes in cholesterol biosynthesis and down-regulation of genes in stress response pathways; however, it was not known whether these changes were directly regulated by PCSK9 or were second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…Regarding other biological functions, genomewide expression analysis studies predict that PCSK9 could be involved in the down-regulation of stress-response genes and specific inflammatory cytokine pathways [16,17]. Additionally, an in vitro study shows that PCSK9 can reduce the levels of the epithelium sodium channel and so modulate the epithelial sodium absorption, thereby PCSK9 may have a role controlling blood pressure [18].…”
mentioning
confidence: 96%
“…Regarding other biological functions, genomewide expression analysis studies predict that PCSK9 could be involved in the down-regulation of stress-response genes and specific inflammatory cytokine pathways [16,17]. Additionally, an in vitro study shows that PCSK9 can reduce the levels of the epithelium sodium channel and so modulate the epithelial sodium absorption, thereby PCSK9 may have a role controlling blood pressure [18].…”
mentioning
confidence: 96%
“…PCSK9 is also involved in numerous biological processes. Microarray studies showed that overexpression of PCSK9 leads to the dysregulation of numerous pathways, including those regulating the cell cycle, apoptosis and inflammation (13,14). In vivo studies also suggested that PCSK9 is implicated in these processes (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The list includes cell-surface proteins as well as intracellular proteins, proteins involved in folding and post-translational modification in the early secretory pathway, proteins involved in vesicle and organelle transport, cytoskeleton as well as cell-adhesion proteins. This global impact of PCSK9/NARC-1 was also demonstrated by two microarrays studies, which implicated this serine protease in many biological pathways [63, 64]. …”
Section: A Novel Form Of Post-translational Regulation In the Ermentioning
confidence: 66%